Discovering students’ preference for classroom activities and teachers’ frequency of activity use - Samperio Sanchez, Nahum (Colombian Applied Linguistics Journal, 2017)
This paper explores the preference students have for classroom activities and the frequency in which teachers include certain classroom activities in their practicum. The study followed a quantitative research methodology by collecting numerical data through a 62-item questionnaire developed from a pool of items gathered from different questionnaires. Analysis indicates a coefficient of reliability of α = .91; data were analyzed with SPSS software. Twenty English language teachers and 263 students of a language school were included in the study. Students’ levels ranged from 1 to 6, the 6th the equivalent to B1 of the Common European Framework (CEF). Results indicated a mismatch between teachers’ frequently used activities and students’ preference of activities; however, there is a match in speaking activities.